ANALISIS PENDAPATAN USAHA TERNAK SAPI DI KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR - Adinda Satria; Jum’atri Yusri; Didi Muwardi (Fakultas Pertanian, Universitas Riau, 2023)
Rumbio Jaya sub-district is one of the areas given cattle assistance by the government. The community took the initiative to do cattle business as a side business to meet their needs and prosper family life. This study aims to analyze the income of cattle business in Rumbio Jaya District, Kampar Regency. The method used in this research is the survey method. Samples were taken using a simple random sampling method for as many as 15 farmers. The average cattle ownership in Rumbio Jaya District is 4.2 heads with a range of 2 to 9 chairs. The results showed that the average income of cattle business in Rumbio Jaya Subdistrict is Rp.18,276,066.62/year which comes from the sale of cattle, value-added cattle, and sales of cattle.